Pós-negritar trajetórias acadêmicas nas encruzilhadas dos saberes: um estudo antropológico das ações afirmativas para pessoas negras na pós-graduação stricto sensu da UFG - Ferreira, Débora Sirno Santos (2023)
This doctoral thesis starts from the following problematization: knowing that most of the Brazilian population is composed of the black population, what factors influence so that only a minority of them are in universities in master's and doctoral courses? The main objective of this ethnography is to investigate, in stricto sensu graduate courses, at the Master's and Doctorate level at UFG, how quota students perceive the quota policy implemented by the university in their experiences. The ethnography carried out with the interlocutors of the UFG stricto sensu postgraduate course showed that all students faced many challenges throughout their academic career, to the point ofmaking many of them drop out, in elementary school, then in high school, with few reaching university. In the academic territory of UFG, it was no different, as well as in their daily lives, they were violated with racist jokes, sexist, homophobic situations, with patriarchy operating over their bodies, the university charging for productions, and, still, the pandemic and social isolation. However, in the face of all these traps strategically prepared by racism, students recognize the importance of being in this place, knowing that many do not manage to reach this stage of study and recognize the rise that this place gives them, both psychologically and socially. and financially. For all this, they share joy when they are recognized for their academic production, and especially when the mother of one of the students, who is their main reference, shares, with joy, the surprise of the boss when she discovers that her maid's son is doctor. We resorted to the anthropology of emotions to explain the context in which these experiences were shared with the researcher and how they crossed her. To better understand ethnic-racial relations in Brazil, it is essential to recognize the relevance and effectiveness of racism and ethnic-racial discrimination, of which groups, black and indigenous people are the target (DIAS, 2012) and which segregate and exclude them from places , spaces and positions. Affirmative actions are intended to combat the accumulated effects of discrimination practiced against black people, which results in economic, educational, political and sociocultural inequalities.